2013
DOI: 10.5194/acpd-13-12991-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of Northern Hemisphere 1950–2010 atmospheric non-methane hydrocarbons

Abstract: The short-chain non-methane hydrocarbons (NMHC) are mostly emitted into the atmosphere by anthropogenic processes. Recent studies have pointed out a tight linkage between the atmospheric mole fractions of the NMHC ethane to the atmospheric growth rate of methane. Consequently, atmospheric NMHC are valuable indicators for tracking changes in anthropogenic emissions, photochemical ozone production, and greenhouse gases. This study investigates the 1950–2010 Northern Hemisphere atmospheric C2-C5 Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Globally, the fossil fuel C 2 H 6 emissions in 2010 decrease by 0.8 Tg compared to 2001. This difference is consistent with the long‐term global decline over this period ending in 2009 [ Franco et al , ; Helmig et al , ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Globally, the fossil fuel C 2 H 6 emissions in 2010 decrease by 0.8 Tg compared to 2001. This difference is consistent with the long‐term global decline over this period ending in 2009 [ Franco et al , ; Helmig et al , ].…”
Section: Discussionsupporting
confidence: 87%
“…The recent literature is summarized in Figure . Briefly, measurements in firn air from Greenland and Antarctica show rising concentrations of C 2 H 6 starting in the 1900s and peaking in the 1970s, followed by a decrease that lasted until the late 2000s [ Aydin et al , ; Helmig et al , ]. The decrease in C 2 H 6 between 1970 and 2006 observed by Aydin et al [] was attributed to a reduction in fugitive emissions from the fossil fuel sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tzompa‐Sosa et al () showed that ethane distributions simulated using these emissions capture the seasonal and spatial distributions seen in surface and aircraft observations from around the world. RONO 2 sensitivity to recent changes in ethane emissions driven by oil and gas extraction (Dalsøren et al, ; Helmig et al, ; Helmig et al, ) is discussed in section .…”
Section: Model Descriptionmentioning
confidence: 99%
“…C 2 -C 3 alkanes are primarily released through natural gas extraction, distribution, and end use, whereas longer chain NMHC are more associated with production and evaporation of liquid fuels. Several recent studies have provided evidence for a reversal in Northern Hemisphere emission trends of NMHC, showing that C 2 -C 5 NMHC increased steadily during 1950 -1970, reached their atmospheric maxima in 1970-1980 and have since declined appreciably to 42-68% of their historic maxima in the Northern Hemisphere (NH) background atmosphere (Simpson et al, 2012;Worton et al, 2012;Helmig et al, 2014a). This decline has been primarily attributed to improved containment technologies in the hydrocarbon fuel production and more stringent emissions regulations associated with the distribution and combustion of petroleum fuels, notably catalytic converters for gasoline road vehicles.…”
Section: Introductionmentioning
confidence: 99%